Pelanggaran Hak Berdaulat Indonesia Oleh Tiongkok Di Laut Natuna Utara Dalam Perspektif Internasional - Nadia vega; Dea Agusti Saputri; Stephen Jonathan Adaran Eben Ezer Sianturi (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2026)
The North Natuna Sea is Indonesia's Exclusive Economic Zone located in the Riau Islands Province, namely Natuna Regency, the emergence of territorial disputes in the North Natuna Sea due to China's claim to the nine-dash line or nine dashed lines. China's violation attitude is part of the country's strategic culture because it is the main factor that causes China's aggressive actions. Where the Republic of Indonesia has sovereign rights to conduct exploration and exploitation, management and conservation of living and non-living natural resources from the seabed and the land beneath it and the water above it and other activities.